MARKETING MANAGEMENT: AN APPROACH BASED ON THE DEFINITION AND CONSIDERATION OF CORPORATE CULTURE - K. Balakleiets; A. Kovalevska (Aktualʹnì Problemi Rozvitku Ekonomìki Regìonu, 2025)
The article comprehensively examines the interplay between marketing management and corporate culture within today's business environment. The research design combines a critical review of the pertinent scholarly literature with logical modelling of the "strategy–culture–marketing" nexus. The authors advance an original definition of corporate culture and outline a conceptual vision of how it can be embedded in marketing management processes. The main findings that define the scientific novelty of this study consist in substantiating the importance of relying on and taking into account both the existing level of corporate culture and the organisation’s objectives for its further development when forming and implementing marketing strategies. This substantiation highlights that such consideration should be integrated into the highest levels of managerial decision-making, through aligning the general elements of the enterprise-wide management system with the marketing management system. Its practical relevance stems from the potential of the proposed approach to serve as a methodological foundation for subsequent investigations and for refining corporate practices across sectors. Although marketing management research is abundant, the interdependence between marketing governance and corporate culture remains underexplored. The article traces the evolution of marketing thought – from the classical views of P. Drucker, F. Kotler and K. Keller to contemporary perspectives endorsed by the American Marketing Association. Special attention is devoted to the marketing mix concept, charting its expansion from the original four Ps to the extended seven Ps and how each element correlates with key components of corporate culture. Issues, directions and prospects for cultural research – values, norms and communication processes – are examined, demonstrating that marketing strategies are highly contingent on cultural maturity. The discussion further considers the roles of corporate, business and functional strategies in marketing management, emphasising that successful strategy execution depends on the level of cultural development. In conclusion, it is necessary to consider cultural factors when developing marketing strategies. A generalised position is formulated according to which marketing management is an approach based on defining and considering corporate culture by identifying specific categories and finding points of contact.